IMPROVING THE PERFORMANCE OF EMMA MOJOKERTO HOSPITAL THROUGH SWOT ANALYSIS AND SKILL-DRIVEN STRATEGY - Astuti, Oktaviana Pitri (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2024)
Hospital management plays a crucial role in ensuring more efficient hospital operations, quality health services, and good financial sustainability. The need for dynamic health services, the role of hospital management is not only limited to administrative aspects, but also involves innovation, adaptation to technological developments, and response to market demands and health policies . This research aims to analyze the SWOT which then forms a Human Resources development strategy through a Skill-Driven strategy for Emma Mojokerto Hospital with several steps, including at the Inching stage Learning and Development will be implemented , at the Progressing stage Workforce Planning will be implemented , at the Transforming stage Reward and Punishment will be implemented , and at the Actualizing stage Organization of Work will be implemented .